PERAN PENYULUH DALAM PENDAMPINGAN TERHADAP KESEHAJTERAAN PETANI KOPI DI DESA BENTENG ALLA KECAMATAN BAROKO KABUPATEN ENREKANG - Aisyah Syafutri; Suardi Suardi; Asri Asri (UNIVERSITAS NEGERI MAKASSAR, 2023)
This study aims to determine the role of extension workers in assisting coffee farmers on the welfare of coffee farmers in Benteng Alla Village, Baroko District, Enrekang Regency. This study uses a qualitative research approach with the type of phenomenological research. The subjects of this study were Fort Alla Coffee Extension and Fort Alla Coffee Farmers. Data was collected by using the method of observation, interviews, and documentation. The techniques used in data analysis are data reduction, data presentation, and conclusion drawing. Triangulation is used to explain the validity of the data by using various sources and methods. The results showed that the extension workers in Benteng Alla Village, Enrekang Regency, carried out their roles as educators, leaders, and advisors. Researchers can conclude that the role of extension workers in assisting coffee farmers on the welfare of coffee farmers in Benteng Alla Village, Baroko District, Enrekang Regency, the focus in the role of the extension worker is the role of the extension worker as an advisor because the role of the extension worker is to provide instructions in the form of how to work which in the end the extension worker is able to generate confidence in his farmers to improve the welfare of coffee farmers.